Semantyka apeth w pismach Klemensa Aleksandryjskiego - Zgraja, Brunon (Vox Patrum, 2008)
The term arete that appears 198 times in the writings of Clement of Alexandria, assumes 15 nuances, among which prevails the common definition of that noun as virtue, with an anthropologic and theocentric reference. The rest of the definitions of arete, belonging chiefly to the ethical vocabulary, complement the terms from other domains: from the military one (talent, virtue), from metaphysics (category, a special atribute), and from botany (perfection of the plant), as well as from functional anatomy (nerve of life).